Baseline characteristics and risk factors for short-term outcomes in 132 COVID-19 patients with diabetes in Wuhan China: A retrospective study. (August 2020) - Li, Yumin; Han, Xiaoyu; Alwalid, Osamah; Cui, Yue; Cao, Yukun; Liu, Jia; Gu, Jin; Wang, Lixia; Fan, Yanqing; Shi, Heshui
Highlights: Patients with FBG (>11 mmol/L) had a higher death rate and were more likely to suffer multiple organ injury than those with glucose level of ≤11 mmol/L. Admission FBG of >11 mmol/l was a potential risk factor for adverse outcomes. Admission d-dimer of ≥1.5 μg/mL contributed to in-hospital deaths. Admission HRCT score of ≥10 was associated with increased odds of in-hospital complications. Abstract: Aims: To investigate the clinical characteristics, laboratory findings and high- resolution CT (HRCT) features and to explore the risk factors for in-hospital death and complications of coronavirus disease 2019 (COVID-19) patients with diabetes. Methods: From Dec 31, 2019, to Apr 5, 2020, a total of 132 laboratory-confirmed COVID-19 patients with diabetes from two hospitals were retrospectively included in our study. Clinical, laboratory and chest CT data were analyzed and compared between the two groups with an admission glucose level of ≤11 mmol/L (group 1) and >11 mmol/L (group 2). Logistic regression analyses were used to identify the risk factors associated with in-hospital death and complications. Results: Of 132 patients, 15 died in hospital and 113 were discharged. Patients in group 2 were more likely to require intensive care unit care (21.4% vs. 9.2%), to develop acute respiratory distress syndrome (ARDS) (23.2% vs. 9.2%) and acute cardiac injury (12.5% vs. 1.3%), and had a higher death rate (19.6% vs. 5.3%) than group 1. In the multivariable analysis, patients with admission glucose of >11 mmol/l had an increased risk of death (OR: 7.629, 95%CI: 1.391–37.984) and in-hospital complications (OR: 3.232, 95%CI: 1.393–7.498). Admission d-dimer of ≥1.5 μg/mL (OR: 6.645, 95%CI: 1.212–36.444) and HRCT score of ≥10 (OR: 7.792, 95%CI: 2.195–28.958) were associated with increased odds of in-hospital death and complications, respectively. Conclusions: In COVID-19 patients with diabetes, poorly-controlled blood glucose (>11 mmol/L) may be associated with poor outcomes. Admission hyperglycemia, elevated d-dimer and high HRCT score are potential risk factors for adverse outcomes and death.